26 Keys to Thriving. - Puutio, T. Alexander; Hogue, Faisal; Hellerstein, David; Godwin, Lindsey; Sullivan, Bill; Haseltine, William A.; Solomon, Eric; Hayes, Steven C.; Smith, Margaret; Ocklenburg, Sebastian; Krueger, Joachim I.; DeGraff, Jeff; et al. (Psychology Today)
The article compiles practical insights from journal contributors on fostering well-being and resilience amid uncertainty. These include the surprising power of a compliment, reason that exceptional adult performers look unremarkable early on, and significance of effective listening to effective discussion.